Monitoring and Controlling Saturation Zones in Heap Leach Piles Using Thermal Analysis - Daud-Albasini, O (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
This manuscript describes a method that is based on the implementation and setup of a mechatronic system that can recognize and detect, through thermal analysis, the zones where heap leaching piles may become locally saturated. Such a condition could trigger the potential of liquefaction, generating local or general collapse in the pile. In order to reduce this potential danger, and therefore achieve full stability in the pile, the irrigation system must be properly controlled; for instance, in potentially saturated zones, the irrigation flow can be reduced or eliminated until the saturation has disappeared. The mechatronic system consists of a hexacopter, equipped with a thermal infrared camera mounted on its structure and pointing down to the ground, which is used to obtain the temperature information of the heat transfer between the heap pile and the environment. Such information is very useful, as the level of saturated zones can then be traced. The communication between the operator of the irrigation system and the mechatronic system is based on a radio-frequency link, in which geo-referenced images are transmitted. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.